INGLIS HÁM QARAQALPAQ TILLERINDE HAYAL HÁM ERKEK SÓYLEW STILINIŃ SALÍSTÍRMALÍ ANALIZI - Kurbanbaeva, D.M. (ILIM hám JÁMIYET, 2025)
The article comparatively is examined gender in English and Karakalpak languages from linguistic, social, and cultural perspectives. According to the research results, emotional and gentle elements predominate in women’s speech, while strictness and logical elements predominate in men’s speech. While gender-neutral tendencies are intensifying in the English language, traditional patriarchal values are still reflected in the Karakalpak language. Genderlect expresses the cultural and social values of society through language.